ORGANIZATION OF THE WORK OF THE UKRAINIAN METEOR OBSERVATION NETWORK (UMON) BASED ON THE USE OF SIGNALS OF BROADCASTING FM-STATIONS - Hrudynin, Borys; Vidmachenko, Anatoliy (Physical and Mathematical Education, 2023)
The question of the development of meteor astronomy in modern Ukraine is considered. The specificity of meteor observation methods requires, first of all, the organization of a network of corresponding observation points. To achieve this goal, it is proposed to combine the scientific and technical capabilities of the participating organizations in the form of the Ukrainian Meteor Observation Network (UMON). UMON is a set of two or more permanently operating observation stations located on the territory of Ukraine, which have the technical and software support for long-base and one-sided meteors observations in different wavelength ranges and conducts such observations. UMON solves the strategic problems of meteor research, the structure and evolution of meteor showers and streams, and the interaction of meteoroids with the Earth's atmosphere, and their chemical composition. The scientific and technical products of UMSM stations are the results of high-precision long-base or one-sided observations of meteors in various wavelength ranges, fundamental and applied scientific and technical research.Based on the signal information of FM transmitters, an analysis of the number of signals reflected from meteors was carried out, depending on their lifetime. The obtained statistics agree with previously known statistics, which is an indicator of the correct selection of meteors by the signals of FM transmitters. A technique for reproducing the analog of the amplitude-frequency characteristic (AFC) based on the spectrum of the FM radio station signal has been developed. The technique uses amplitude modulation caused by Fresnel interference on the meteor trail, which leads to the loss of the signal at the output of the FM receiver when the signal/interference ratio at its input is lower than the lower threshold of the frequency demodulator. The time sequence of the FM radio signal reflected from the meteor is an important distinguishing feature and can be used to develop an algorithm for the automatic recognition of meteors by the FM radio signal.Formulation of the problem. Observations of meteors help solve several problems of modern astronomy and physics, both of a fundamental nature and those of practical importance. All this knowledge can be obtained thanks to the processing and analysis of the results of meteor observations obtained using optical and radar methods. Observations of meteors in the radio range, which are based on the effect of the reflection of radio waves from the ionized trace of a meteor, should be systematic and carried out with the help of an extensive meteor observation network.Materials and methods. The operation of an automated complex of meteor observations in the radio range using the method of receiving echoes of signals from over-the-horizon radio stations (FM, Frequency Modulation) has been organized, which was successfully launched on August 5, 2019. To obtain the results presented for consideration in this paper, we used theoretical (analysis of scientific literature, special works on the theory of the movement of cosmic bodies, statistical data processing) and experimental (use of an automated complex of meteor observations in the radio range using the method of receiving echoes of signals from over-the-horizon radio stations) methods.The results. A statistical analysis of the signals received from the radio tracks of observations of meteor incursions into the Earth's atmosphere existing in Ukraine was carried out. The results of the Glukhiv (Ukraine) - Kielce (Poland) radio route, to which the author of the article is directly related, are presented.Conclusions. As described in the work, the modern capabilities of individual scientific institutions of Ukraine to carry out research in the field of meteor astronomy make it possible to carry out fundamental and applied scientific and technical research of meteor phenomena at a high level, to obtain the results of high-precision basic or one-sided observations of meteors in various wavelength ranges.
Keywords: meteor; meteor shower; Ukrainian meteor observation network